HUBUNGAN KONSUMSI KOPI, OBESITAS SENTRAL, DAN MEROKOK DENGAN HIPERTENSI PADA MASYARAKAT USIA DEWASA DI WILAYAH KERJA PUSKESMAS 1 DENPASAR BARAT - Dewi, Ni Nyoman Ratna; Sutiari, Ni Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024DO - 10.24843/ACH.2024.v11.i03.p21, 2025)
Hypertension is an abnormal increase in blood pressure in the blood vessels continuously for more than one period. Lifestyle is a causal factor that can increase the risk of hypertension. The purpose of this study was to determine the relationship between coffee consumption, central obesity and smoking with hypertension in the adult community in the Working Area of Health Center 1 West Denpasar. This research was conducted in the Working Area of Health Center 1 West Denpasar using primary data and secondary data. The research design used was cross sectional with a sample of 85 adults with an age range of 35-45 years. Data collection techniques used are interviews and measurements. The data analysis used was descriptive analysis and bivariable analysis using the chi square test. The results showed that central obesity (p-value <0.001) and smoking (p-value <0.001) were significantly associated with hypertension, while coffee consumption did not have a significant relationship (p-value = 0.194). It is necessary to provide education to the public regarding healthy lifestyles such as coffee consumption, obesity and smoking. Keywords: Hypertension, coffee consumption, central obesity, smoking